One-Enzyme RTX-PCR for the Detection of RNA Viruses from Multiple Virus Genera and Crop Plants - Hoffmeisterová, Hana; Kratochvílová, Kateřina; Čeřovská, Noemi; Slavíková, Lucie; Dušek, Jakub; Muller, Karel; Fousek, Jan; Plchová, Helena; Navrátil, Oldřich; Kundu, Jiban Kumar; Moravec, Tomáš (Viruses, 2022)
Reverse transcription PCR (RT-PCR) is a popular method for detecting RNA viruses in plants. RT-PCR is usually performed in a classical two-step procedure: in the first step, cDNA is synthesized by reverse transcriptase (RT), followed by PCR amplification by a thermostable polymerase in a separate tube in the second step. However, one-step kits containing multiple enzymes optimized for RT and PCR amplification in a single tube can also be used. Here, we describe an RT-PCR single-enzyme assay based on an RTX DNA polymerase that has both RT and polymerase activities. The expression plasmid pET_RTX_(exo-) was transferred to various E. coli genotypes that either compensated for codon bias (Rosetta-gami 2) or contained additional chaperones to promote solubility (BL21 (DE3) with plasmids pKJE8 or pTf2). The RTX enzyme was then purified and used for the RT-PCR assay. Several purified plant viruses (TMV, PVX, and PVY) were used to determine the efficiency of the assay compared to a commercial one-step RT-PCR kit. The RT-PCR assay with the RTX enzyme was validated for the detection of viruses from different genera using both total RNA and crude sap from infected plants. The detection endpoint of RTX-PCR for purified TMV was estimated to be approximately 0.01 pg of the whole virus per 25 µL reaction, corresponding to 6 virus particles/µL. Interestingly, the endpoint for detection of TMV from crude sap was also 0.01 pg per reaction in simulated crude plant extracts. The longest RNA fragment that could be amplified in a one-tube arrangement was 2379 bp long. The longest DNA fragment that could be amplified during a 10s extension was 6899 bp long. In total, we were able to detect 13 viruses from 11 genera using RTX-PCR. For each virus, two to three specific fragments were amplified. The RT-PCR assay using the RTX enzyme described here is a very robust, inexpensive, rapid, easy to perform, and sensitive single-enzyme assay for the detection of plant viruses.
Keywords: DNA-dependentní DNA-polymerasy; Sensitivity and Specificity; senzitivita a specificita; RTX-PCR; Phylogeny; Plant Viruses; Potyvirus; rostlinné viry; Luteovirus; Plant Diseases; RNA-viry; DNA-Directed DNA Polymerase; Nepovirus; Tobamovirus; Capillovirus; one-step RT-PCR; Crops, Agricultural; RNA Viruses; Tritimovirus; fylogeneze; Trichovirus; nemoci rostlin; polymerázová řetězová reakce; Polymerase Chain Reaction; Polerovirus; Foveavirus; virus detection; Potexvirus; zemědělské plodiny